CRISPR/Cas9-Based Gene Editing Using Egg Cell-Specific Promoters in Arabidopsis and Soybean - Zheng, Na; Li, Ting; Dittman, Jaime D.; Su, Jianbin; Li, Riqing; Gassmann, Walter; Peng, Deliang; Whitham, Steven A.; Liu, Shiming; Yang, Bing (Frontiers in Plant Science, 2020)
CRISPR/Cas9-based systems are efficient genome editing tools in a variety of plant species including soybean. Most of the gene edits in soybean plants are somatic and non-transmissible when Cas9 is expressed under control of constitutive promoters. Tremendous effort, therefore, must be spent to identify the inheritable edits occurring at lower frequencies in plants of successive generations. Here, we report the development and validation of genome editing systems in soybean and Arabidopsis based on Cas9 driven under four different egg-cell specific promoters. A soybean ubiquitin gene promoter driving expression of green fluorescent protein (GFP) is incorporated in the CRISPR/Cas9 constructs for visually selecting transgenic plants and transgene-evicted edited lines. In Arabidopsis, the four systems all produced a collection of mutations in the T2 generation at frequencies ranging from 8.3% to 42.9%, with egg cell-specific promoter AtEC1.2e1.1p being the highest. In soybean, function of the gRNAs and Cas9 expressed under control of the CaMV double 35S promoter (2x35S) in soybean hairy roots was tested prior to making stable transgenic plants. The 2x35S:Cas9 constructs yielded a high somatic mutation frequency in soybean hairy roots. In stable transgenic soybean T1 plants, AtEC1.2e1.1p:Cas9 yielded a mutation rate of 26.8%, while Cas9 expression driven by the other three egg cell-specific promoters did not produce any detected mutations. Furthermore, the mutations were inheritable in the T2 generation. Our study provides CRISPR gene-editing platforms to generate inheritable mutants of Arabidopsis and soybean without the complication of somatic mutagenesis, which can be used to characterize genes of interest in Arabidopsis and soybean.